2022
DOI: 10.1039/d2dt00193d
|View full text |Cite
|
Sign up to set email alerts
|

A dual-function Cd-MOF with high proton conduction and excellent fluorescence detection of pyridine

Abstract: Metal-organic frameworks have great potential in the field of proton conducting materials and fluorescent probes due to their structural tunability and designability. A novel water-stable metal organic framework material [Cd2(Hdpb)(H2O)3]...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…S8, ESI†), which is a common electrical behavior for proton-conducting materials. 24,25 The proton conductivity significantly increases from 4.1 × 10 −8 S cm −1 at 40% RH to 3.2 × 10 −5 S cm −1 at 97% RH (Table S7, ESI†), indicating the critical role of water molecules as proton carriers for boosting the proton transport process.…”
Section: Resultsmentioning
confidence: 99%
“…S8, ESI†), which is a common electrical behavior for proton-conducting materials. 24,25 The proton conductivity significantly increases from 4.1 × 10 −8 S cm −1 at 40% RH to 3.2 × 10 −5 S cm −1 at 97% RH (Table S7, ESI†), indicating the critical role of water molecules as proton carriers for boosting the proton transport process.…”
Section: Resultsmentioning
confidence: 99%
“…Multifunctional materials exhibiting multiple properties in a single crystalline material have attracted extensive attention in material science and chemistry. Metal–organic frameworks (MOFs) are considered to be a promising platform for designing multifunctional materials. , Due to the diversities of compositions including metal cations or clusters and bridging ligands, the structures and properties of MOFs can be relatively easily modulated and controlled by the synthetic conditions and selection of different structural units. ,, Recently, multifunctional MOF materials with proton conduction and luminescent sensing properties have received more attention due to their potential usage in clean energy as well as environmental monitoring fields. …”
Section: Introductionmentioning
confidence: 99%
“…To obtain the targeted multifunctional MOFs, selecting the appropriate metal centers and organic ligands is very crucial . It is well known that MOFs composed of d 10 metal centers and functional ligands can display excellent luminescence and proton conduction performances, which provide a chance to construct dual-functional MOFs with luminescent sensing and proton conduction. ,, It has been demonstrated that the organic components of MOFs are crucial in determining the structures and properties of MOFs. ,,, Organic phosphonic acid (RPO 3 H 2 ) ligands have three oxygen atoms and can link multiple metal ions with diverse coordination modes, which have been well used for building phosphonate-based MOFs with different structures and properties. , Because of the strong coordination abilities of the phosphonic acid ligands, metal phosphonates generally exhibit better thermal and chemical stabilities than other MOFs. , , Therefore, metal phosphonates provide an opportunity for the construction of multifunctional MOFs with stable structures and multiple properties. In addition, the synthetic method of introducing second ligands has also been broadly used in the construction of multifunctional MOFs. ,,, Based on hard and soft acid–base theory, the transition-metal ions prefer to coordinate with the nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations